Patient rights and the doctor-patient relationship (Colombia Medica, 1987)
The patient's principal rights are reviewed, and comments are given on how the doctor-patient relationship can be improved. Emphasis is placed on individuality when addressing these rights, such as the right to pain, free choice of doctor, costs of care, freedom to accept or reject procedures, the right to truth and information, the right to privacy, and, finally, the right to die with dignity.